Prevalence and socio-demographic and obstetric factors for anaemia among pregnant women in second and third trimester in a tertiary hospital of Delhi - Sharma, Nishal; Kishore, Jugal; Gupta, Monika; Singla, Himal; Dayma, Rohini; Sharma, J. B. (International Journal Of Community Medicine And Public Health, 2024)
Background: Anaemia during pregnancy continues to be a major public health problem especially in developing nations like India. The study was performed to assess the prevalence and severity of anaemia and the associated socio-demographic and obstetric factors during pregnancy in a tertiary referral hospital of Delhi, India. Method: This cross sectional study was carried out on 430 pregnant women in second and third trimester of pregnancy using systematic random sampling attending antenatal clinic of Vardhman Mahavir Medical College and Safdarjung Hospital of Delhi. A predesigned and structured questionnaire proforma was used to collect information regarding socio-demographic and obstetric factors. Haemoglobin levels were estimated using Hemocue method. Statistical analysis was carried out using STATA version 18.0 statistical software. Results: The overall prevalence of anaemia during pregnancy was 48.84% with 25.81% mild anaemia, 15.81% moderate anaemia, 6.98% severe anaemia and 0.24% very severe anaemia. Anaemia was found to be more common in younger women (<25 years) and in joint family. Anaemia was more commonly seen in low socio-economic status, low family income and in illiterate and primary education. Anaemia especially severe anaemia was more common in third gravidas and above. Anaemia was more common with advancing gestation. Anaemia was more common with no or irregular antenatal care and with no or single tetanus toxoid injection. Conclusions: The prevalence of anaemia is high in Delhi. Regular and timely antenatal care, improving socio-economic status and having lesser children can reduce prevalence of anaemia during pregnancy.